The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1111/j.1471-4159.1987.tb13130.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Phosphorylation Sites for Different Kinases in the Microtubule‐Associated Protein MAP2

Abstract: The phosphorylation of microtubule-associated protein 2 (MAP2) by four different kinases was studied in vitro to determine whether MAP2 is phosphorylated in its tubulin binding region or in the microtubule projection portion. Fragments corresponding to both regions of MAP2 were produced not only by chymotrypsin or trypsin digestion, but also using pepsin, a broad chain-specificity protease, a result supporting previous notions of the two-domain structure of MAP2. The position of these two functional domains wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Halpain and colleagues have observed that calcium influx through NMDA receptors caused a significant decrease of MAP‐2 phosphorylation via the activation of calcineurin (phosphatase 2B) (Halpain and Greengard, 1990 ; Quinlan and Halpain, 1996). MAP‐2 is well known to stabilize microtubular structures, but its phosphorylation status is highly critical for its affinity to microtubules (Hernández et al, 1987 ; Brugg and Matus, 1991). Indeed, a decrease in MAP‐2 phosphorylation led to an increased microtubular stability (Illenberger et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Halpain and colleagues have observed that calcium influx through NMDA receptors caused a significant decrease of MAP‐2 phosphorylation via the activation of calcineurin (phosphatase 2B) (Halpain and Greengard, 1990 ; Quinlan and Halpain, 1996). MAP‐2 is well known to stabilize microtubular structures, but its phosphorylation status is highly critical for its affinity to microtubules (Hernández et al, 1987 ; Brugg and Matus, 1991). Indeed, a decrease in MAP‐2 phosphorylation led to an increased microtubular stability (Illenberger et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…MAP-2 phosphorylation by CAMKII inhibits microtubule assembly [90,108]. Additionally, in vitro and in vivo data showed that several MAP-2 serine residues represent a substrate for protein kinase C (PKC) [92,94,109], which is involved in synaptic plasticity and memory processes [110,111]. When MAP-2 is phosphorylated by PKC its ability to bind microtubules and promote microtubule assembly is reduced [112].…”
Section: Maps Phosphorylationmentioning
confidence: 99%
“…In neurons one third of the cytosolic PKA is associated with microtubules and PKA itself was firstly identified in brain microtubule preparation co-purified with MAP-2 [84][85][86][87][88]. PKA can phosphorylate MAP-2 in vitro in 11 different serines residues [85,86,[89][90][91][92][93] and most of them can also be phosphorylated in vivo [94][95][96]. MAP-2 phosphorylation by PKA decreases the binding of MAP-2 to tubulin [97], reduces tubulin assembly [97] and inhibits the calpain-mediated proteolysis of MAP-2 [98,99].…”
Section: Maps Phosphorylationmentioning
confidence: 99%
“…However, studies with domainspecific antibodies indicate that the binding domain may occupy as much as one-third of the molecule's length (Gottlieb & Murphy, 1985). MAP 2 fragments containing the tubulin binding domain have been suggested to contain the N-terminal of the molecule (Hernandez et al, 1987) and they appear to be relatively basic compared to the projection domain or to undigested MAP 2 (Sattilaro, 1986;Flynn et al, 1987).…”
Section: Mapmentioning
confidence: 99%